2013
DOI: 10.1371/journal.pone.0068520
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus Patients Contain Significantly Less IgM against Mono-Methylated Lysine than Healthy Subjects

Abstract: Post-translational modifications on proteins are important in biological processes but may create neo-epitopes that induce autoimmune responses. In this study, we measured the serum IgG and IgM response to a set of non-modified or acetyl- and methyl-modified peptides corresponding to residues 1–19 of the histone 3 N-terminal tail in systemic lupus erythematosus (SLE) patients and healthy subjects. Our results indicated that the SLE patients and healthy subjects produced antibodies (Abs) to the peptides, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…The levels of total IgM in SLE patients were also lower than those in healthy subjects ( Fig 6C ), whereas the levels of total IgG in SLE and other rheumatic patients were higher than those in healthy subjects ( Fig 6D ). As previously reported [ 12 ], there was no correlation between the levels of anti-Kme IgM and disease activity of SLE ( P = 0.5774, Fig 6E ). There was also no correlation between the levels of anti-Kme3 IgM and disease activity of SLE ( P = 0.3276, Fig 6F ).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The levels of total IgM in SLE patients were also lower than those in healthy subjects ( Fig 6C ), whereas the levels of total IgG in SLE and other rheumatic patients were higher than those in healthy subjects ( Fig 6D ). As previously reported [ 12 ], there was no correlation between the levels of anti-Kme IgM and disease activity of SLE ( P = 0.5774, Fig 6E ). There was also no correlation between the levels of anti-Kme3 IgM and disease activity of SLE ( P = 0.3276, Fig 6F ).…”
Section: Resultssupporting
confidence: 81%
“…The purified antibodies were highly specific. We previously showed that IgM anti-Kme reacted to peptides that contained mono-methylated lysine and did not react to peptides that had no methylation or had di- or tri-methylated lysine [ 12 ]. To determine whether the IgM reacted with methyl groups on other residues, we tested its reactivity to methylated DNA and mono-methylated arginine that was on a peptide corresponding to the 1–19 N-terminal residues of histone H3 (H3 1-19 R2me, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unexpected lack of specificity for anti-H3p/H3p me reactivity in our assay might be due to a decreased accessibility within the circulating nucleosome/apoptotic microparticle, for which we found evidence in a previous study [6]. Another explanation might be the reactivity against methylated residues in plasmas from healthy individuals, which has been described before for IgM [32]. Importantly, we demonstrated that the modified peptides H4p ac and H2Bp ac show an increased specificity and sensitivity compared to their unmodified counterpart.…”
Section: Discussionmentioning
confidence: 51%